Zadovoljstvo s stanovanji v naselju Braamfischerville v Sowetu in kakovost življenja v njih - Moolla, Raeesa (Urbani izziv, 2011)
The African National Congress (ANC) government initiated the building of Reconstruction and Development Programme (RDP) housing units in order to provide housing to the previously disadvantaged and to address the severe housing backlog that has developed in South Africa in recent years. However, in spite of the good intentions, there has been profound criticism with regardto the inferior building standards and quality of these housing units, as well as the lack of services and amenities in these development projects. The research for this paper was conducted in 2008. The residents of the Braamfischerville area in Soweto were chosen as sample respondents. Aspects such as demographic data, monthly income and monthly expenses were ascertainedfor each household using a systematic questionnaire. The level of satisfaction with regard to specific housing attributes such as the house itself, windows, doors, the roof and so on was rated using a five-point LikertScale and determined from interviews. It was also found that residents identified proximity to basic services and amenities as being equally important as the appearance of the property as a contributing factor leading to satisfaction. It therefore proved to be important to establish basic amenities near newly developed communities. The findings revealed that there were specific grievances concerning the quality of the housing units and access to basic services and amenities that reduced the level of satisfaction in terms of housing and that consequently had a negative impact on the quality of life of Braamfisherville residents.
Keywords: javne storitve; Južnoafriška republika; kvaliteta; kvaliteta življenja; Soweto; stanovanja; stanovanjska naselja; zadovoljstvo